2000
DOI: 10.1067/mtc.2000.110250
|View full text |Cite
|
Sign up to set email alerts
|

Marrow stromal cells for cellular cardiomyoplasty: Feasibility and potential clinical advantages

Abstract: Different cell sources have been used as donor cells for cellular cardiomyoplasty. Our findings indicate that marrow stromal cells can also be used as donor cells. In an appropriate microenvironment they will exhibit cardiomyogenic phenotypes and may replace native cardiomyocytes lost by necrosis or apoptosis. Because marrow stromal cells can be obtained repeatedly by bone marrow aspiration and expanded vastly in vitro before being implanted or used as autologous implants, and because their use does not call f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
197
0
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(207 citation statements)
references
References 26 publications
2
197
0
6
Order By: Relevance
“…Novel surgical therapies include left ventricular remodelling, mechanical circulatory assistance and, more recently, isolated cell transplantation or gene therapy (111)(112)(113)(114)(115)(116). The advent of cell transplantation provides great promise for the future because it may be a useful adjunct to several of the previously mentioned therapies.…”
Section: Arnold Et Almentioning
confidence: 99%
“…Novel surgical therapies include left ventricular remodelling, mechanical circulatory assistance and, more recently, isolated cell transplantation or gene therapy (111)(112)(113)(114)(115)(116). The advent of cell transplantation provides great promise for the future because it may be a useful adjunct to several of the previously mentioned therapies.…”
Section: Arnold Et Almentioning
confidence: 99%
“…BrdU labelled cells survived, transdifferentiated into cardiomyocytes and induced angiogenesis at 4 weeks after cell transplantation. It had been shown that cardiac milieu (Wang et al, 2000) had important effect on myogenesis and angiogenesis. The ischemia myocardium may produce some myogenic factors, such as TNF, IL6 and CRP.…”
Section: Discussionmentioning
confidence: 99%
“…Hematopoietic stem cells (SC) reportedly have the ability to transdifferentiate into epithelial cells [Krause et al, 2001;Badiavas et al, 2003a;Badiavas and Falanga, 2003b], cardiac myocytes [Hamill et al, 1981;Klug et al, 1996;Li et al, 1996;Mar et al, 1997;Scorsin et al, 1997;Tomita et al, 1999;Wang et al, 2000;Orlic et al, 2001a,b;Yeh et al, 2003;Madeddu et al, 2004;Tomita et al, 2004], liver cells [Petersen et al, 1999;Lagasse et al, 2000;Theise et al, 2000a,b], bone [Becker et al, 1999], lung cells [Aliotta et al, 2004], neurons [Brazelton et al, 2000], and skeletal myocytes [Gussoni et al, 1999]. This response, with few exceptions, is seen only in response to injury.…”
mentioning
confidence: 99%
“…To date, investigations of myocardial repair have fallen into the following categories: (1) the transplant of bone marrow, mesenchymal stem cells, fetal cardiac myocytes, and myocytes into mice or rats [Hamill et al, 1981;Klug et al, 1996;Li et al, 1996;Mar et al, 1997;Scorsin et al, 1997;Tomita et al, 1999;Wang et al, 2000;Orlic et al, 2001b]; (2) the transplant of human SC into immunodeficient mice with results suggesting that transdifferentiation into various cardiomyocytic cells that facilitate repair does occur [Yeh et al, 2003;Madeddu et al, 2004;Tomita et al, 2004;Zhang et al, 2004]; and (3) clinical studies using directly injected unseparated bone marrow [Strauer et al, 2002;Tse et al, 2003], separated populations containing hematopoietic SC or CD34þ purified cells [Stamm et al, 2003;Kang et al, 2004], or myoblasts [Smits et al, 2003] with results supporting a clinical benefit. In one study, improvement was also observed in patients given intracoronary infusion of granulocyte-colony stimulating factor (G-CSF)-primed peripheral blood stem cells (PBSC) and G-CSF injections; however, the G-CSF administration was associated with an unexpectedly high rate of in-stent restenosis [Kang et al, 2004].…”
mentioning
confidence: 99%